2018
DOI: 10.1101/324574
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated RNA-seq and sRNA-seq revealed differences in transcriptome between susceptible and resistant tomato responding toFusarium oxysporum

Abstract: Tomato wilt disease caused by Fusarium oxysporum f. sp. 22 lycopersici (FOL) is a worldwide destructive disease of tomato. As exploring gene 23 expression and function approaches constitute an initial point for investigating 24 pathogen-host interaction, we performed RNA-seq and sRNA-seq analysis to 25 unravel regulated genes and miRNAs in tomato infected by FOL. Differentially 26 expressed (DE) protein coding gene and miRNA gene profiles upon inoculation 27 with FOL were presented at twenty-four hours post-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
(87 reference statements)
1
0
0
Order By: Relevance
“…This is consistent with a recent study, using microarrays, wherein 16 different WRKY transcription factors were found upregulated in tomato plants infected with Fol, among which WRKY36 and WRKY37 stood out [29]. Thus, it is possible that the plethora of WRKY transcription factors represents the evolution of specialized responses against different Fol strains [34,35], and more generally, against different pathogens [30]. WRKY transcription factors were not found upregulated in the cultivars CT2 or IAC391.…”
Section: Induction Of Defense-related Genes During Fol Infectionsupporting
confidence: 91%
“…This is consistent with a recent study, using microarrays, wherein 16 different WRKY transcription factors were found upregulated in tomato plants infected with Fol, among which WRKY36 and WRKY37 stood out [29]. Thus, it is possible that the plethora of WRKY transcription factors represents the evolution of specialized responses against different Fol strains [34,35], and more generally, against different pathogens [30]. WRKY transcription factors were not found upregulated in the cultivars CT2 or IAC391.…”
Section: Induction Of Defense-related Genes During Fol Infectionsupporting
confidence: 91%